Evaluasi Penyelenggaraan Angkutan Udara Lebaran 2009 di Bandara Internasional Sultan Hasanuddin Makassar - Dina Yuliana; Endang Dwi Agustini (WARTA ARDHIA, 2009)
The number of passenger air transport movements during Lebaran 2009 in Sultan International Airport Makassar reached 126,907 passengers, or up 126.91% from the previous year. Institutions associated with the implementation of transport Lebaran is Adbandara, PT. Angkasa Pura I (Persero), Police, TNI-AU, Public Health, Security and Scout. Problems in implementation include the supervision of the airlines to travel agents about searching Seat -is very weak resulting in user satisfaction lack of air transport services with information assurance seats, the plane delays still occur either because of technical and operational factors, waiting lists, Check in Counter.